Impact of Print Media on Public Opinion and State Policy Regarding the Global War on Terror in Pakistan - Muhammad, Ahsan (2023)
The tragic 9/11 attacks have shaken the entire world, since then US & allies have initiated global war on terror (GWOT) to eliminate terrorism. Pakistan joined GWOT when then President Musharaf decided to join US in GWOT. Pakistan is facing a severe wave of terrorism, resulting in several deaths, injuries, and damaging consequences in economy, peace, and security. During GWOT, the role of media is criticized for playing a negative role that hampers efforts of respective governments. This research explores the impact of Pakistani print media on public opinion and state policy on GWOT. The research questions are which agendas are promoted and issues are framed by the print media of Pakistan on GWOT? What was the role of the media during GWOT? what was impact of framed issues and promoted agendas on public opinion and state policy? The objectives of the study are to analyze the agendas (agenda setting) by Pakistani media during global war on terror. To identify the role of Pakistani media during global war on terror. To examine the influence of media’s agenda setting and issue framing on GWOT towards public opinion in Pakistan and towards Pakistan’s policy. This is a qualitative research study, where case study research design is used. Two important case studies of Pakistan’s GWOT are used, i.e., Musharraf’s decision to join GWOT in 2001, and Operation Zarb e Azb. The population of study includes articles, editorials, and stories from two leading newspapers of Pakistan, i.e., Dawn and The Nation along with secondary sources. Content analysis with the aid of thematic analysis is used to interpret, categorize, and analyze collected data. The findings highlighted that Pakistani print media presented dominant antiwar agendas and framed issues negatively on GWOT. Pakistani print media played a negative role on GWOT. Pakistani print media impacted public opinion and policy matters of Pakistan in negative manner resulted in public protests and undesired policy shifts. The key implications of this study are that findings will allow policy makers and stakeholders including media outlets to device effective, efficient, and sustainable policies regarding security, media coverage and other related matters during GWOT. This research can help policy makers in evaluating and reformulating national integration and counterterrorism measures in Pakistan.